Management of the Quran Memorization Program at Ulil Albab Islamic Elementary School - Nurrohmah, Siti; Maryanto; Eliyanto; Fauziah, Muna (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to examine the management of the Quran memorization program at Ulil Albab Islamic Elementary School, Kebumen. Qualitative research was used in this study with the subjects of the principal, head of memorization, ustadz/ah, and students of Quran memorization at Ulil Albab Islamic Elementary School, Kebumen. Data were collected from observation, interviews, and documentation. Data were analyzed by reducing data, presenting data, and making conclusions. The findings of the study showed that the management of the Quran memorization program at Ulil Albab Islamic Elementary School, Kebumen had been implemented optimally through the stages of planning, organizing, implementing, and supervising. Program planning was carried out by setting program objectives, appointing a program coordinator, setting memorization targets, preparing a schedule, preparing a strategy, and preparing program facilities and infrastructure. Organization was overcome by forming an organizational structure accompanied by the main tasks of each member of the organization. The Quran memorization program is held every Monday to Saturday from 09.00 to 09.45 with memorization, tajwid, and book study materials. Program supervision is carried out by the foundation's supervisors and administrators through preliminary, ongoing, and feedback supervision.